Robert W. Kates’ Reader:: A New Map of Sustainability Science and Technology - Clark, William (Sustainability in Debate, 2011)
KATES, Robert W., ed. 2010. Readings in Sustainability Science and Technology. CID Working Paper No. 213. Center for International Development, Harvard University. Cambridge, MA: Harvard University, December 2010.